Elemen Persekitaran Sistem Pensijilan Kosmetik Halal Malaysia dari Perspektif Sistemik - Khairul Akmaliah Adham; Nadiah Mahmad Nasir; Nur Sa’adah Muhamad; Intan Fatimah Anwar; Farah Laili Muda @ Ismail (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2026)
Indexed by Scopus